Die sowjetischen Kriegsgefangenen der Technischen Brigade Mineralöl: Der Einsatz sowjetischer Mineralölfachkräfte an der Ostfront zwischen Ideologie und wehrwirtschaftlichem Interesse - Matthias Puchta (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– One of the Wehrmacht's main goals in the Caucasus were the oil fields. A special unit for the Caucasus operation was the "Technische Brigade Mineralöl" (Mineral Oil Technical Brigade). The large volume of surviving files from the TBM allows us to glean new insights into the German prisoner of war system at the brigade level. The treatment of the Soviet petroleum specialists is an absolute exception in the German POW system regarding Soviet POWs. The article traces the reasons for this at the intersection of ideology and pragmatism. The files, when viewed as a whole, enable us to make statements about the TBM POWs over the course of their existence. Furthermore, the special treatment of petroleum specialists is contextualized within the broader military-economic environment of the Wehrmacht.
Keywords: H56; L71; N44; N94; Q34; 330; Soviet POWs; Army Group A; Technische Brigade Mineralöl; Caucasus; petroleumindustry; military economy; Case Blue; forced labor; occupation